High Levels of FOXP3+ Regulatory T Cells in Gastric MALT Lymphoma Predict Responsiveness to Helicobacter pylori Eradication. Issue 5 (1st April 2013) - Iwaya, Yugo; Kobayashi, Motohiro; Momose, Masanobu; Hiraoka, Nobuyoshi; Sakai, Yasuhiro; Akamatsu, Taiji; Tanaka, Eiji; Ohtani, Haruo; Fukuda, Minoru; Nakayama, Jun
Abstract Background Although Helicobacter pylori eradication is a first‐line treatment of gastric MALT lymphoma, roughly 25% of patients do not respond to treatment. CD4+ FOXP3+ regulatory T (Treg) cells regulate immune responses in physiological conditions and various inflammatory conditions, including H. pylori‐associated diseases. Our goal was to determine how Treg cells affect responsiveness to H. pylori eradication therapy. Materials and methods We performed dual immunohistochemistry for CD4 and FOXP3 to evaluate the prevalence of FOXP3+ Treg cells in the stomach of 63 patients with MALT lymphoma and 55 patients with chronic active gastritis. Receiver operating characteristic analysis was carried out to determine the best cut‐off point in differentiating H. pylori eradication responders from nonresponders. Results Both the FOXP3+/CD4+ cell ratio and the absolute number of FOXP3+ cells per high‐power field in MALT lymphoma were significantly greater in H. pylori eradication responders compared with nonresponders, suggesting that Treg cells function in regression mechanisms of MALT lymphomas. Cut‐off points with good sensitivities and specificities were obtained to predict eradication outcome. Conclusions A high number of Treg cells or a high ratio of Treg cells to the total number of CD4+ T cells in gastric MALT lymphoma could predict responsiveness to eradication therapy.